Vanishing points - Leggott, Michele J. (Auckland University Press, 2017)
"Vanishing Points concerns itself with appearance and disappearance as modes of memory, familial until we lose sight of that horizon line and must settle instead for a series of interconnecting arcs. It is full of stories caught from the air and pictures made of words. It stands here and goes there, a real or an imagined place. If we can work out the navigation the rest will follow"--Back flap